Women Entrepreneurship and Innovation in Higher Education : Opportunities and Challenges in India - A Review - Archana, M. S.; Vijaya Kumar, M. N.; Shyamasundar, M. S. (Journal of Engineering Education Transformations, 2022)
In the recent years, Entrepreneurship and Innovation have taken new dimension due to increase in the globalization and liberalization. Women Entrepreneurs are the ones who start a venture or a business activity generating jobs for others. The three major factors that are playing important role in women entrepreneurship are : Firstly, internal factors such as individual's attitude towards risk taking or family encouragement, secondly external factors such as government support or reward system and finally the third factor is education & competencies. According to 2016 report of Small Industry Development Bank of India (SIDBI), following southern Indian states such as Karnataka, Tamil Nadu, Kerala, Andhra Pradesh and Maharashtra have witnessed more than 50% of all women led small scale industrial units in India. The GDP of a nation increases as the women of the country progress in the field of entrepreneurship and innovation. Women have to be given equal chance as men in the field of entrepreneurship as most of the talented women end up with responsibilities at home. Despite facing a lot of socio-economic problems, women entrepreneurs and innovators have become successful. With a little more encouragement from the government , a change can be brought in how higher education institutions fosters entrepreneurship and innovation in women students and hence more and more women entrepreneurs are developed. To build the confidence and to promote innovation in women, a separate category of ranking for women institutions were included in Atal Ranking of Institutions on Innovation and Achievement (ARIIA) 2020, where a total of 674 institutions participated. The Indian higher education system has expanded at a fast pace by adding more than 20,000 colleges and more than 8 million students in the last decade and as of today, India has more than 800 universities. According to the AICTE 2016 report, there are over 10,500 engineering colleges and polytechnics in the country with an intake capacity of about 22,00,000 students. The conversion rate of women entrepreneurs are still very low, in spite of these many educational institutions. There are a lot of challenges with women entrepreneurship in India such as social obstacles , patriarchal society, lack of exposure, lack of confidence, lack of education facilities, no agenda in life, degree of financial freedom, risk taking abilities, lack of professional education, lack of interaction with successful entrepreneurship, lack of balance between family and career, lack of skills and finance in economically rich and poor women, no awareness about the capacities, problems working with male workers and so forth. This paper focuses on literature review of women entrepreneurship and Innovation in Higher Education in India and the key findings are highlighted.